2011
DOI: 10.1007/s10457-011-9413-4
|View full text |Cite
|
Sign up to set email alerts
|

Exotic tree species displace indigenous ones on farms at intermediate altitudes around Mount Kenya

Abstract: Agroforestry systems are potentially suitable for conservation of tree genetic resources. Farmers around Mt. Kenya usually integrate trees into their farm. Large parts of these trees seem to be of exotic origin, whereas indigenous species have priority for conservation. This study aimed at determining on-farm richness, composition and frequency of indigenous and exotic woody species around Mount Kenya to assess the suitability of farms for the conservation of indigenous tree species. 265 onfarm plots of 0.5 ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 25 publications
(31 reference statements)
2
15
0
Order By: Relevance
“…Only Sesbania spp., M. lutea and C. macrostachyus are ranked among the 10 most abundant tree species in the farms studied. This observation is consistent to results obtained from western and central Kenya (Kindt et al, 2006;Kehlenbeck et al, 2011;Lengkeek et al, 2005) whereby exotic species had tree count compared to indigenous species but lower species count. The existence of high abundance of exotics demonstrates deliberate planting and choice (Simons and Leakey, 2004).…”
Section: Agroforestry Practices In Smallholder Farmssupporting
confidence: 91%
See 1 more Smart Citation
“…Only Sesbania spp., M. lutea and C. macrostachyus are ranked among the 10 most abundant tree species in the farms studied. This observation is consistent to results obtained from western and central Kenya (Kindt et al, 2006;Kehlenbeck et al, 2011;Lengkeek et al, 2005) whereby exotic species had tree count compared to indigenous species but lower species count. The existence of high abundance of exotics demonstrates deliberate planting and choice (Simons and Leakey, 2004).…”
Section: Agroforestry Practices In Smallholder Farmssupporting
confidence: 91%
“…For example, Carsan (2012) recorded 165 tree species on smallholder coffee farms in Central Kenya with mean species richness of 17 species per farm. Kehlenbeck et al (2011) found a mean tree species richness of 17 per farm and Lengkeek et al (2005) observed a mean of 54 species per farm. The species richness of 44 we found in our study area and a mean of 8 tree species per farm are therefore relatively low compared to other studies in agricultural landscapes of Kenya.…”
Section: Agroforestry Practices In Smallholder Farmsmentioning
confidence: 97%
“…Thus, in southern Bahia, Brazil, farmers often plant non-native rubber (Hevea brasiliensis) and jackfruit (Artocarpus heterophyllus) trees rather than native timber and fruit trees for shade in their cocoa farms (Schroth et al, 2011); in Costa Rica, Eucalyptus species have become popular as coffee shade (Tavares et al, 1999;Schaller et al, 2003); and in Ghana, cocoa and coffee farmers wishing to diversify into timber production often prefer South American Cedrela odorata or Asian Tectona grandis to native species (Ruf, 2011). Similar preferences for planting exotic tree species on farm land have also been observed in other tropical regions (Dewees, 1995;Elouard et al, 2000;Takaoka, 2008a,b;Ambinakudige and Sathish, 2009;Nath et al, 2011;Kehlenbeck et al, 2011;Tefera et al, 2014;Nyaga et al, 2015;Valencia et al, 2015). In addition to the threat of declining environmental quality and ecosystem services caused by exotic species monocultures, diversity and continuity of the tree canopy may be compromised, thus preventing wildlife migration across agroforests and between nearby forest fragments (Perfecto et al, 1996;Vandermeer and Perfecto, 2007;Schroth et al, 2011).…”
Section: Introductionmentioning
confidence: 82%
“…Farmers worldwide have contributed substantially towards this diversity by planting trees that provide economic value, food security and environmental improvement (Dewees, 1995;Scherr, 1995;Akinnifesi et al, 2006;Takaoka, 2008a;Anglaaere et al, 2011;Kehlenbeck et al, 2011;Goodall et al, 2015;Nyaga et al, 2015). However, a recent globally observed threat to farmland biodiversity is the ongoing transformation of traditional complex agroforests into simpler land use forms dominated by exotic species, which may eventually culminate in unshaded crop monocultures (Siebert, 2002;Peeters et al, 2003;Ruf, 2011;Jha et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Agroforestry systems contribute significantly to the conservation of biodiversity and its genetic resources in fragmented landscapes (Kehlenbeck et al 2011;Nath et al 2011;Jose 2012;Souza et al 2012). Such systems contain up to 50 % of the diversity found in natural forests (Nobel and Dirzo 1997).…”
Section: Introductionmentioning
confidence: 99%